PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY (TS-TS) TERHADAP HASIL BELAJAR IPA PADA SISWA - Fauzi Fadliansyah (LPPM Universitas Bina Bangsa, 2023)
Based on data obtained from interviews with the homeroom teacher in class IV SDIT Bina Bangsa, information was obtained that in social studies subjects there were still many students whose grades had not reached the KKM, due to students' low understanding of the subject matter. The things that become obstacles in learning are because the learning process that occurs is designed without varied learning models and the lack of use of learning media in the teaching and learning process so that students are not enthusiastic in learning and students also experience difficulties in understanding the material presented. The purpose of this research is (1) to determine the effect of implementing the Two Stay Two Stray (TS-TS) learning model on student learning outcomes in social studies subjects on animal metamorphosis. (2) to determine the significant differences between the social studies learning outcomes of experimental class and control class students. (3) to determine students' responses to the application of the Two Stay Two Stray (TS-TS) learning model. The type of research used was Quasi-experimental, with a population of all SDIT Bina Bangsa students for the 2022-2023 academic year, sampling using a purposive sampling technique. Data collection techniques in this research used tests and non-tests. Data analysis was carried out at the beginning of learning (pre test) and after learning (post test). The research results show that the average learning outcome of students in the experimental class which uses the Two Stay Two Stray (TS-TS) learning model is 86.00 and the average learning outcome in the control class which uses the conventional learning model is 63.33. The results of hypothesis testing with the help of SPSS version 26 using the Independent Simple t Test statistics show a significance value of 0.000<0.05 so it can be concluded that Ho is rejected, which means that there is an influence of using the Two Stay Two Stray (TS-TS) learning model on science learning outcomes on students class IV SDIT Bina Bangsa